TEMPORAL ANALYSIS OF RIVER WATER QUALITY USING POLLUTION INDEX: A CASE STUDY OF THE REJOSO RIVER, PASURUAN REGENCY - Yanitra, Fahmi Alpha; Semedi, Bambang; Anggayasti, Wresti Listu; Dewi, Juwita Ratna (Journal of Environmental Engineering and Sustainable Technology, 2025)
Assessing temporal variations in river water quality is essential for understanding pollution dynamics and supporting effective water resource management, particularly in regions experiencing increasing anthropogenic pressure. This study investigates temporal trends in the Rejoso River, Pasuruan Regency, East Java, during 2022–2025 using the Pollution Index (PI) method. Water quality data were obtained from routine monitoring by the Environmental Agency and analyzed through compliance assessment, spatial distribution analysis, and non-parametric statistical methods, including the Mann–Kendall test and Sen’s slope estimator. The results show that several parameters, particularly biochemical oxygen demand (BOD), phosphate, and fecal coliform, frequently exceeded Class II water quality standards, indicating dominant organic and domestic pollution sources. Spatially, water quality declined from upstream to downstream, with the middle section identified as the most polluted due to cumulative anthropogenic activities such as domestic discharge and agricultural runoff. Temporal analysis revealed increasing trends in key pollution indicators, especially BOD and COD, suggesting a gradual increase in pollutant loads. The Pollution Index classified the river as predominantly lightly polluted, with a temporary improvement in 2024 followed by deterioration in 2025. These findings highlight increasing environmental pressure and the need for integrated water quality management strategies.